2014
DOI: 10.1155/2014/298295
|View full text |Cite|
|
Sign up to set email alerts
|

Chicken Collagen from Law Market Value By-Products as an Alternate Source

Abstract: There has been much interest in investigating possible means of making collagen from underutilized chicken by-products and it will lead to an alternate source of collagen for use in various industries such as pharmaceuticals, cosmetics, biomedical materials, and the food industry. The objective of this research was to find methods to extract collagen from chicken skins and bones to compare the corresponding yield differences and analyze their properties. Collagen extracted by acetic acid, citric acid, alkali, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…Broilers are young chicken (Gallus gallus domesticus) of either sex of six to eight weeks of age. There are studies suggesting the potential of functional protein extraction from by-products of poultry industry (Fauzi et al, 2016;Mohammad et al, 2014;Munasinghe et al, 2014). The study suggests that collagen -another example of parent protein molecule -could be extracted from chicken skins and bones, which then can be utilized in various fields such as pharmaceuticals, biomedicine and food.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broilers are young chicken (Gallus gallus domesticus) of either sex of six to eight weeks of age. There are studies suggesting the potential of functional protein extraction from by-products of poultry industry (Fauzi et al, 2016;Mohammad et al, 2014;Munasinghe et al, 2014). The study suggests that collagen -another example of parent protein molecule -could be extracted from chicken skins and bones, which then can be utilized in various fields such as pharmaceuticals, biomedicine and food.…”
Section: Introductionmentioning
confidence: 99%
“…The study suggests that collagen -another example of parent protein molecule -could be extracted from chicken skins and bones, which then can be utilized in various fields such as pharmaceuticals, biomedicine and food. As collagen shares similar characteristics with elastin, it is worth investigating the potential of chicken skin for elastin extraction (Mecham, 2008;Munasinghe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further, they suggested that more molecular cross-links between collagen and other components can be broken by the additional digestion with pepsin. After comparing yields of five different extraction procedures with 0.5 M acetic acid, 0.5 M citric acid, alkali extraction, one-step acetic acid and pepsin extraction and two-step acidic acid and pepsin extraction [10], one-step acetic acid and pepsin extraction was performed to extract collagen to form collagen films because of the high yield of collagen (38.7%).…”
Section: Collage Extraction Using One-mentioning
confidence: 99%
“…NaCl. Five milliliters of the collagen solution (8 mg/mL) was mixed with 5 mL of NaCl solution of different concentrations (2,4,6,8,10, and 12%). The highest solubility (0.11 mg/mL) was obtained at 2% NaCl (Table 2).…”
Section: Chicken Collagen Solubility At Different Concentration Ofmentioning
confidence: 99%
“…Food, pharmaceutical, cosmetic, biomedical and nutraceutical industries are such common industries which used collagen in various applications (Munasinghe et al, 2014;Schmidt et al, 2016). Usually, collagen is used in form of gelatin and collagen peptide or also known as collagen hydrolysate (Aberoumand, 2012).…”
Section: Introductionmentioning
confidence: 99%